Acute nephrology for the critical care physician - Straaten, Heleen M. Oudemans-van; Forni, Lui G.; Groeneveld, A. B. Johan; Bagshaw, Sean M.; Joannidis, Michael (Springer, 2015)
This practical guide provides the reader with answers to important clinically relevant questions regarding the evaluation and management of acute kidney injury (AKI). All aspects of critical care nephrology are covered, from pathophysiology and diagnosis to prevention and treatment. The questions considered relate to a wide range of issues, such as: How do I diagnose AKI? How can I protect the kidney in clinical practice? How do I manage patients with AKI? When should I initiate and how do I perform renal replacement therapy (RTT)? Which type of RTT is most appropriate for my patient? Should I give specific nutrients? In addition to providing practical guidelines and treatment algorithms, the book includes calculators for continuous RRT and anticoagulant dosing. The authors are internationally renowned experts in the fields of Intensive Care Medicine and Nephrology and all contributions are written in a clear and concise style and have been peer reviewed. Acute Nephrology for the Critical Care Physician will serve as a very useful source for intensivist internists, anesthesiologists and nephrologists involved in the management and treatment of critically ill patients at risk of or affected by AKI.